Contribution of classical complement activation and IgM to the control of Rickettsia infection. Issue 6 (13th November 2021) - Dahmani, Mustapha; Cook, Jack H.; Zhu, Jinyi C.; Riley, Sean P.
Abstract: Pathogenic Rickettsia are obligate intracellular bacteria and the etiologic agents of many life‐threatening infectious diseases. Due to the serious nature of these infections, it is imperative to both identify the responsive immune sensory pathways and understand the associated immune mechanisms that restrict Rickettsia proliferation. Previous studies have demonstrated that the mammalian complement system is both activated during Rickettsia infection and contributes to the immune response to infection. To further define this component of the mammalian anti‐ Rickettsia immune response, we sought to identify the mechanism(s) of complement activation during Rickettsia infection. We have employed a series of in vitro and in vivo models of infection to investigate the role of the classical complement activation pathway during Rickettsia infection. Depletion or elimination of complement activity demonstrates that both C1q and pre‐existing IgM contribute to complement activation; thus implicating the classical complement system in Rickettsia ‐mediated complement activation. Elimination of the classical complement pathway from mice increases susceptibility to R . australis infection with both increased bacterial loads in multiple tissues and decreased immune activation markers. This study highlights the role of the classical complement pathway in immunity against Rickettsia and implicates resident Rickettsia ‐responsive IgM in the response to infection. Abstract : Pathogenic Rickettsia are extremely dangerous bacteria that parasitize the cytoplasm of the mammalian vasculature. Due to the serious nature of these infections, it is imperative to both identify the responsive immune sensory pathways and understand the associated immune mechanisms that restrict bacterial growth. This manuscript identifies a component of the complement system and pre‐existing IgM as key contributors to immune recognition of these bacteria.